Production of moisturizing cream enriched with rosemary essential oil obtained via enzymatic fungal extraction (Research, Society and Development, 2021)
The extraction of essential oils from aromatic plants is a process that presents considerable disadvantages such as the use of highly expensive equipment, high quantity of organic solvents with great potential for contamination, besides the need for a large quantity of raw material to obtain a small fraction of oil. In this perspective, the development of sustainable methodologies for the research of natural products, such as essential oils, with the purpose of promoting the increase in the yield of essential oil extraction, the reduction in the cost of production and the increase in its quality is growing. Thus, with the purpose of optimizing the extraction of the essential oil of Rosmarinus officinalis L., achieving simultaneously a greater yield and purity of the same, this work aimed to analyze the production of moisturizing cream from rosemary essential oil extracted by the application of enzymes produced by filamentous fungi of the genus Rhizopus sp. The results showed that from the application of multi-enzyme extracts (EMB) an optimization of 83.24% was reached in the extraction of rosemary oil, which also obtained the physical, chemical and organoleptic parameters desired and required according to the current legislation. In addition, a cosmetic topical formulation was developed with the addition of the extracted essential oil that also met the specifications and quality standards required by the Brazilian Pharmacopoeia.